2021
DOI: 10.1021/acs.chemmater.0c03202
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalenothiophene Imide-Based Polymer Donor for High-Performance Polymer Solar Cells

Abstract: Naphthalenothiophene imide (NTI), bearing six-membered imide and a five-membered aromatic ring, was synthesized by a one-step Suzuki reaction in high yield. NTI is an electron-deficient monomer that could effectively lower the HOMO energy level of the polymer. Thus, the NTI-based polymer PNTB1 has a low-lying HOMO energy level (−5.42 eV) without introducing any F or Cl group into the polymer backbone. By mixing with a nonfullerene electron acceptor Y6, solar cell devices exhibit power conversion efficiency as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…Moreover, the properties can be well controlled by changing the D or A units to tune the internal electron pushÀpull effects. [11,12] In particular, we also note that many outstanding DÀA polymer donors, such as PBDB-T, PM6, PM7, etc., are based on benzodithiophene (BDT) as D unit and 1,3-bis(thiophen-2-yl)-5,7-bis(2-ethylhexyl) benzo-[1,2-c:4,5-c'] dithiophene-4,8-dione (BDD) as A unit [13][14][15] Further, the properties can also be modulated through the substituents attached at the conjugated backbone. Introducing an electron-withdrawing substituent into the polymer has been demonstrated as an effective method.…”
Section: Introductionmentioning
confidence: 72%
“…Moreover, the properties can be well controlled by changing the D or A units to tune the internal electron pushÀpull effects. [11,12] In particular, we also note that many outstanding DÀA polymer donors, such as PBDB-T, PM6, PM7, etc., are based on benzodithiophene (BDT) as D unit and 1,3-bis(thiophen-2-yl)-5,7-bis(2-ethylhexyl) benzo-[1,2-c:4,5-c'] dithiophene-4,8-dione (BDD) as A unit [13][14][15] Further, the properties can also be modulated through the substituents attached at the conjugated backbone. Introducing an electron-withdrawing substituent into the polymer has been demonstrated as an effective method.…”
Section: Introductionmentioning
confidence: 72%
“…76 In 2021, Wu et al reported a pentacyclic acceptor unit naphthalene-thiophene imide (NTI) and developed a series of D–A copolymers with low HOMO energy levels due to the electron-deficient imide group and aromatic five-membered ring of NTI. 77 For example, PNTB6-Cl based on chlorinated BDTT and NTI with a linear hexyl chain showed poor solubility in chloroform due to its stronger intermolecular interactions and shorter π–π stacking distance. Consequently, the layer-by-layer (LBL) processed OSCs based on PNTB6-Cl :N3 exhibited an impressive PCE of 17.59% with excellent batch-to-batch reproducibility.…”
Section: Other Polymersmentioning
confidence: 99%
“…[10][11][12] Meanwhile, the complex aromatic cyclization or uorination reactions of the above-mentioned materials with state-of-the-art PCEs, such as uorinated 2D-conjugated benzo[1,2-b:4,5-b ′ ]dithiophene (BDT) 8 and alkylthiophene linked DTBT, 13 may thereby obstruct their future commercialization due to the cost issue. To reduce the synthetic cost, some efforts have been made to shorten synthesis steps, 14,15 employ simplied building block units, [16][17][18] or control reaction conditions and simplify purication methods, 19 among which designing novel photovoltaic materials with non-fused-ring chemical structures and without any expensive functional groups has been considered as an effective way to solve the critical cost issue.…”
Section: Introductionmentioning
confidence: 99%